Mechanical and corrosion properties of TaN coatings by N2/Ar flow ratio processes. (1st September 2013) - Ji, X; Zhou, X Y; Teng, J Y; Mi, Y M; Zhang, C M
<x xml:space="preserve">Abstract</x> To optimise the performance of silicon diffusion barriers, TaN coatings were deposited through reactive magnetron sputtering at various N2/Ar flow ratios (4, 8, 12, 18 and 24%). The effects of the flow ratios on the structures, morphologies, corrosion and mechanical properties of the coatings were investigated in detail. The results show that the flow ratios had strong effects on the phase transformations from cubic to hexagonal phases in the coatings. Furthermore, the results of the morphology study indicated that the flow ratio was a vital parameter in determining the grain growth and the formation of TaN nanoparticles. Finally, the best improvement in corrosion and mechanical properties was found in the coating at 24%, which could be due to the occurrence of phase change and nanosized particles.